MENINGKATKAN KEPERCAYAAN DIRI ANAK MELALUI METODE PROYEK PADA ANAK USIA 4-5 TAHUN DI TK EDUCATION 21 KULIM KECAMATAN PAYUNG SEKAKI PEKANBARU - Kenny Anthia Kenny Anthia; Daviq Chairilsyah Daviq Chairilsyah; Hukmi Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on preliminary observations conducted by researchers at children in kindergarten Education 21 Kulim of Payung Sekaki Pekanbaru, there are still many visible lack of confidence shown the child when the child arrives at school when mother leaves them. Still to be accompanied parents. Children always refused to become the leader of the line, when in classroom doing question-answer and children only nodded and shook his head without daring expression, storytelling in front of the class is still accompanied by the teacher, the child does not want to show his work. Field conditions do not correspond to what the objectives of the school. As for the purpose of this study to determine the confidence of children aged 4-5 years in kindergarten Payung Sekaki Pekanbaru before the implementation of the project method, to determine whether there is influence methods of the project on the confidence of children aged 4-5 years in kindergarten Payung Sekaki Pekanbaru and to know how improvement occurs. This research is a classroom action research (PTK), which is done in 2 cycles. Data collection used in this study is in the form of observation sheet. The number of samples in this study were 20 people consisting of 9 boys and 11 girls. Based on the results of data processing and observations of confidence has increased in each cycle. The percentage increase in the confidence of children aged 4-5 years using project in kindergarten Education 21 Kulim Payung Sekaki Pekanbaru can be seen from the prior measures the percentage of the value obtained with an average of 38.67% with less criteria. Once repaired in the first cycle obtained by the percentage of the average value of 45.22% with less criteria, on the second cycle increased with the percentage of the average value obtained a value of 74.11%, it can be seen that the methods of the project can increase the confidence of children 4-5 years of age with sufficient criteria.Keywords: Confidence, Project Methods, Early Childhood